Proceso de atención de enfermería en paciente de 27 años con sepsis uterina posterior a un legrado quirúrgico. - Díaz Álava, Naomi Patricia (2021)
Uterine sepsis is a frequent infection that can occur in gynecological patients, leading to a greater risk of complications if it is not diagnosed and treated in time. Age, the use of immunosuppressive agents, invasive procedures and the number of resistant microorganisms are the main precursors to this pathology. In this case, a 27-year-old multiparous patient is presented, who three days after performing a surgical curettage in a private health home, presents a picture of hypogastric pain, transvaginal bleeding and fever. A post-curettage infection is diagnosed, after performing a gynecological evaluation and laboratory tests, antibiotic treatment is prescribed with satisfactory evolution and departure on the eighth day. Sepsis is a significant cause of maternal morbidity and mortality. Among the most important causes are endometritis, chorioamnionitis, surgical wound infection, septic abortion and mastitis, since the latter can cause a systemic inflammatory response. The main pathogen associated with maternal mortality is group A streptococcus, other frequent microorganisms include Escherichia coli, group B streptococcus, staphylococcus and anaerobes.